Model Latihan Standing Broad Jump with Elastic Band Resistance dengan Standing Broad Jump and Squat Jump Sequence untuk Meningkatkan Daya Ledak Otot Tungkai - Rustiawan, Hendra; Huda, Wahdatul; Sutisna, Nana; Risma, Risma (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
The purpose of this study was to understand the increasing rate of leg explosive power. The population used were the thirty Putra students of SMK Komputama Majenang in the province of Cilacap, who were divided into two study groups. The sample preparation technique used the entire sampling technique. The research method used was the pre-experimental two-group design. The test instrument used was the standing broad jump. Based on data analysis using SPSS series 24, the data collection results consist of 1) The standing wide jump with elastic band resistance has a significant impact on the day-to-day change in head height of students at SMK Komputama Majenang Kabupaten Cilacap. 2) The standing wide jump and squat leap sequences have a significant impact on the students at SMK Komputama Majenang Kabupaten Cilacap's ability to increase their day-to-day walking speed. 3) There were notable differences.